1998
DOI: 10.1016/s0029-7844(98)00114-8
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Early Postoperative Feeding in Gynecologic Oncology Patients Undergoing Intra-abdominal Surgery

Abstract: Early postoperative feeding in gynecologic oncology patients undergoing intra-abdominal surgery is safe and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…In the USA, POI is estimated to cost between $5000 and $10 000 or a total of $1 billion per year due to discomfort, prolonged hospital stay and increased treatment costs . The incidence of POI after gynaecological surgery has a mean incidence of 10–15% (range of 5–25%) . The aetiology and pathogenesis of POI is multifactorial; therefore, a multimodal approach is required to counteract the morbidity of POI.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, POI is estimated to cost between $5000 and $10 000 or a total of $1 billion per year due to discomfort, prolonged hospital stay and increased treatment costs . The incidence of POI after gynaecological surgery has a mean incidence of 10–15% (range of 5–25%) . The aetiology and pathogenesis of POI is multifactorial; therefore, a multimodal approach is required to counteract the morbidity of POI.…”
Section: Introductionmentioning
confidence: 99%
“…When postoperative ileus develops, it is usually transient and clinically not significant. Therefore, feeding within 24 hours after laparotomy is tolerated, and the feed is absorbed 4-5. …”
Section: Introductionmentioning
confidence: 99%
“…The randomized clinical trials of early enteral feeding in POI have showed the controversial results 17 . Some studies showed that early feeding reduced the duration of POI, 23–25 while others failed to show any differences 26–29 . Our current study demonstrated that feeding stimulated gastric motility in the group of manipulation although its motility was impaired before the feeding.…”
Section: Discussionmentioning
confidence: 42%